Gene Expression Essential for Myostatin Signaling and Skeletal Muscle Development Is Associated With Divergent Feed Efficiency in Pedigree Male Broilers - Lassiter, Kentu; Kong, Byungwhi Caleb; Piekarski-Welsher, Alissa; Dridi, Sami; Bottje, Walter Gay (Frontiers in Physiology, 2019)
Background: Feed efficiency (FE, gain to feed) is an important genetic trait as 70% of the cost of raising animals is due to feed costs. The objective of this study was to determine mRNA expression of genes involved in muscle development and hypertrophy, and the insulin receptor-signaling pathway in breast muscle associated with the phenotypic expression of FE. Methods: Breast muscle samples were obtained from Pedigree Male (PedM) broilers (~8 wk old) that had been individually phenotyped for FE between 6 and 7 wk of age. The high FE group gained more weight but consumed the same amount of feed compared to the low FE group. Total RNA was extracted from breast muscle (n = 6 per group) and mRNA expression of target genes was determined by real-time quantitative PCR. Results:Targeted gene expression analysis in breast muscle of the high FE phenotype revealed that muscle development may be fostered in the high FE PedM phenotype by down-regulation several components of the myostatin signaling pathway genes combined with upregulation of genes that enhance muscle formation and growth. There was also evidence of genetic architecture that would foster muscle protein synthesis in the high FE phenotype. A clear indication of differences in insulin signaling between high and low FE phenotypes was not apparent in this study. Conclusion: These findings indicate that a gene expression architecture is present in breast muscle of PedM broilers exhibiting high FE that would support enhanced muscle development-differentiation as well as protein synthesis compared to PedM broilers exhibiting low FE.